Segurança da água em bacias hidrográficas: formulação de um modelo institucional. - Pinheiro, Maria Inês Teixeira (2015)
This research proposes an institutional framework for water security in watersheds, inspired by the Water Safety Plan for Human Supply (PSA) in Portugal. The model consists of two stages: the diagnosis of polluting sources and the development of an institutional matrix, relating to each source of pollution, its generating agent in its class, the supervisory agent and the regulator, and the identification of the requirement, or not, the environmental license and the grant. We used the model proposed in the watershed of Acarape the Middle dam in the state of Ceará, where they were identified and classified sources of pollution, its geographical location in relation to the areas of permanent preservation, direct and indirect influence, and additional basin area (ABC). After systematization, it was observed that most of the 82 points, potentially generating pollution, is located upstream and / or around the weir. The area had more sources of pollution was the ACB. Point sources are prevalent in the basin which can facilitate monitoring and control. It was noted, though, based on Institutional Matrix, the main generating agents of pollution are CAGECE dealership (with continuous discharge of effluents from the treatment plants water and sewage) and municipalities (slaughterhouses, health services, solid waste, among others). The main supervisory agent, according to legislation, is the environmental agency SEMACE. It highlighted the importance of the interaction of water safety plan in river basins with other sectoral plans - National Plan of Basic Sanitation, Regional and Local, Municipal Master Plan, Local Plan of Social Housing, Water Resources Plan, Plan Watershed, Municipal Environmental Plan, among others. The institutional model developed in this research can be an important instrument of quality management of water in river basins.